Reproductive Health Behavior with Premarried Sex on the Street Children in Pekanbaru City - Yulrina Ardhiyanti; Kiki Megasari (Institute of Computer Science (IOCS), 2022)
Street children in their lives face various problems, including mental health and safety problems, physical and psychological violence, crime and premarital sexual behavior. Deviant behavior in Indonesian teenagers nowadays, there are many teenagers who have premarital sex so that unwanted pregnancies and abortions occur. This study aims to analyze reproductive health behavior with premarital sex on street children in Pekanbaru City. This study uses a qualitative approach, observation techniques, in-depth interviews, literature and documentation. The data collection technique used a snowball technique (snowball). There are 6 informants, 3 main informants, 1 key informant, and 2 supporting informants. The results of the research are reproductive health behavior with premarital sex carried out by street children due to the influence of peers and the influence of the mass media, they consider premarital sex to be normal and the right of every individual. It is hoped that related parties will provide reproductive health education on premarital sex behavior through social media and limit access to pornographic sites, equip teenagers with religious values ​​so that teenagers are afraid to commit deviant acts.